ANALYSIS OF CONSUMER ATTITUDES TOWARD BRAND EQUITY IN IJA KROENG PRODUCTS - Rahmi Rahmi; Nelly Nelly (Departemen Manajemen, Universitas Syiah Kuala, 2018)
Brand equity is the value of a brand, depend the extent to which the brand has high loyalty, the quality that is accepted by consumers and able to add more value to consumers. A strong brand equity can help a company in an effort to attract potential customers as well as efforts to establish good relationships with consumers and can eliminate consumer doubts about brand quality. One of the factors that influences brand equity is the attitude of consumers towards a brand. This study was aimed to analyse consumer attitudes towards brand equity in Ija Kroeng products in Banda Aceh. The sample of this study was 100 respondents. The data used in this study was quantitative data. The results showed that consumer attitudes had a significant effect on brand equity in Ija Kroeng products in Banda Aceh, it was proven by the attitude of consumers as factors that influence brand equity, which was proven by 84.9% of research results and the remaining 15.1 % explained by other variables outside of this research, for instance product quality, brand awareness, brand associations, etc. While partially consumer attitudes have a significant effect on brand equity in Ija Kroeng products in Banda Aceh, with the value of tcountttable(2,051 1,984). That partially consumer attitudes have a significant effect on brand equity in Ija Kroeng products in Banda Aceh. This means that consumer attitudes can significantly increase brand equity in Ija Kroeng products in Banda Aceh. Key wordsConsumer attitudes, Brand equity